Pemanfaatan Teknologi dalam Membangun Sumber Daya Manusia yang Lebih Berkualitas di Yayasan Pendidikan Islam Tajaul Karomatu Desa Situ Gadung Tangerang - Endang Susilo Wardani; Eti Ariyanti; Laila Irawati (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The rapid advancement of technology has significantly influenced the development of human resources, particularly in educational institutions. Many schools and foundations face challenges in integrating technological tools effectively to enhance teaching, learning, and administrative processes. In this context, the Community Service Program (PKM) was implemented at Yayasan Pendidikan Islam Tajaul Karomatu, Desa Situ Gadung, Tangerang, aiming to optimize the use of technology to improve the quality of human resources, including both teachers and students. The primary objective of the PKM was to provide knowledge, practical skills, and guidance on utilizing technology for educational and personal development. The PKM was carried out on November 8, 2025, involving six lecturers from Universitas Pamulang as facilitators and 38 participants, consisting of students and teachers. The activities employed a combination of material presentations, practical exercises, discussions, and question-and-answer sessions, structured across three main stages: preparation, implementation, and reporting. During the preparation stage, facilitators conducted needs assessment, prepared training materials, and coordinated with school management. The implementation stage focused on hands-on practice with technological tools, enhancing digital literacy, and fostering problem-solving skills, while the reporting stage involved evaluating the participants’ understanding and the overall effectiveness of the program. The results of the PKM showed a significant improvement in participants’ ability to utilize technology for learning and teaching, enhanced engagement in classroom activities, and increased motivation among students and teachers to integrate digital tools in daily practice. This program demonstrates that technology-based interventions can effectively strengthen human resource quality in educational settings.